PEMBELAJARAN WACANA DALAM BAHASA INDONESIA SEKOLAH DASAR - Murtiningsih Murtiningsih (MAJALAH ILMIAH PEMBELAJARAN, 2009)
Problem that mainly discussed in this paper is about discourse in Bahasa Indonesia. The aim of this writing is to explain the learning of discourse in bahasa indonesia. On the disscusion author only discusing a simple scoope of it, so that the reader could easily understood. Range of discussion will be the learning of discourse in bahasa Indonesia, element of discourse, kind of fine discourse and it’s example.Discourse are differ in to two, they were oral and anal discourse. Oral discourse is a comment that present in the communication process between the communicator and the communican. Anal or written discourse is an idea from the communican and communicator that expressed in a note. Discourse were formed by words, sentences and paragraph. Those three element were fused and concerned to form a unity of words that intact, complete and harmony.Fine discourse was determined by its prelude and closing sentences, topic, aim, theme, title, cohession and coherence. Several example of discourse in bahasa Indonesia are dialog discourse, monolog discourse, naration discourse, exposition discourse, argumentation and persuation discourse.